TOURISM DEVELOPMENT PLANNING IN THE REGION ALONG THE BANKS OF THE RED RIVER, HANOI - Nguyễn, Văn Tăng; Lê, Việt Hà (Trường đại học văn hóa Hà Nội, 2023)
Abstract. After the complete reunification of Vietnam, the first session of the 6th National Assembly in 1976 designated Hanoi as the capital of the Socialist Republic of Vietnam. Having a thousand-year history, having the advantage of being the leading political, administrative, economic, cultural, scientific, educational and diplomatic center of the country, Hanoi is increasingly developing in many areas, including the development of tourism. Every area of Hanoi is a valuable tourist resource that can be used for economic development and tourism. The area on both banks of the Red River is one of these areas. The article discusses plans for the development of tourism on the two banks of the Red River in Hanoi on the following aspects: tourist resources, cultural values and tourist values. The idea of orientation of the use of the value of the Red River in Hanoi in the future is laid.